The geomorphological impacts of impoundments, with particular reference to tributary bar development on the Keiskamma River, Eastern Cape - McGregor, Gillian Kathleen (Rhodes University, Faculty of Science, Department of Geography, 2000)
The primary aim of this research was to develop and test a conceptual model of the geomorphological impacts of river regulation, based on a review of relevant international literature. It was motivated by the fact that there is very little local information on the topic, and it was intended that the model might provide a starting point for assessing the impact of impoundments on South African river systems. At present most research in South Africa on the impact of impoundments is undertaken from an ecological perspective. In order to manage our water resources sustainably it is necessary to have a better understanding of our river systems. South Africa is characterised by a variable climatic regime and, in order to supply water to the various user sectors of the nation, dams have to be larger than elsewhere in the world, to trap most of the mean annual runoff and provide a reliable water store (Alexander, 1985). South African dams have been designed to reduce the variability of a naturally variable regime. The impact of flow regulation in dryland rivers has been described as 'ecologically catastrophic at every level.' It is therefore hardly surprising that the impact of these dams on the natural functioning of rivers is substantial. The conceptual model showed that there are many responses to river impoundment, which are varied and complex, both in time and space. Responses or secondary impacts depended on the nature and degree of the primary impact or process alteration, on the sediment and flow regime of the river. High flows were affected in all cases and low flows were affected in most cases. The simplest form of change was Petts' (1979) concept of 'accommodation' of the regulated flow within the existing channel form. More complex responses occUrred where the channel perimeter was unstable, or where tributaries introduced fresh sediment loads. The river could adjust its long profile, cross sectional area and substrate composition by aggradation or degradation. The conceptual model was used in the Building Block Methodology to predict impoundment impacts at Instream Flow Requirement workshops on the Berg, Komati and Bivane rivers. It was also used in assessing the impact of the Sandile Dam on the Keiskamma river. Tributary junctions were identified as likely sites of change, and the morphology of bars at these junctions was investigated. Due to the number of variables affecting the sediment and flow regime in the system, and due to the fact that the primary impacts were not substantial, it was not possible to come to any decisive conclusions. It would seem that the dam is well located in the catchment, and, because the water is not heavily utilised, the secondary impacts are not great. The conceptual model was found to be a useful basic tool which might contribute to a better understanding of our river systems, and ultimately to improved sustainable resource management.
Keywords: Rivers--South Africa--Regulation; Rivers--South Africa--Regulation--Environmental aspects; Rivers--South Africa--Eastern Cape; Geomorphology--South Africa--Eastern Cape